Human experience : philosophy, neurosis, and the elements of everyday life - Russon, John, 1960- (SUNY series in contemporary continental philosophy., 2003)
"Beginning with a study of the nature of perception, embodiment, and memory, Russon investigates the formation of personality through family and social experience. He focuses on the importance of the feedback we receive from others regarding our fundamental worth as persons, and on the way this interpersonal process embeds meaning into our most basic bodily practices: eating, sleeping, sex, and so on. Russon concludes with an original interpretation of neurosis as the habits of bodily practice developed in family interactions that have become the foundation for developed interpersonal life, and proposes a theory of psychological therapy as the development of philosophical insight that responds to these neurotic compulsions."--Jacket